Ecological and Behavioural Drivers of Human–Sloth Bear Coexistence in and around Jessore Wildlife Sanctuary, Gujarat - Rathod, Kanakba; Jhala, Devendrasinh; Munjpara, Sandeep (Indian Forester, 2025)
This study is about human–Sloth Bear (Melursus ursinus) interactions in Banaskantha district, Gujarat, India, within and around Jessore Sloth Bear Sanctuary (JWS) from January 2023 to December 2024. Conducted in four villages (Kapasiya, Vera, Balundra, Vavdhara), the study employed transect sampling (20 transects, 29 km effort), camera trapping (30 cameras, 30 days/site), structured interviews (n=181), and focus group discussions to assess Sloth Bear presence and human–Sloth Bear dynamics. Of 211 detections, 63.0% (n=133) occurred in forested areas, 19.9% (n=42) near water sources, and 1.4% (n=3) near human food sources, indicating a strong forest preference. Human sightings (n=147) were higher in anthropogenic areas (e.g., 17.0% in settlement peripheries), differing significantly from ecological detections (χ² = 42.58, p < 0.00001). Sloth Bear showed crepuscular/nocturnal activity (83% detections from 18:00–06:00), with 60% in summer due to water scarcity. Conflicts, often involving females with cubs in summer (χ² = 16.28, p = 0.012), decreased due to artificial water sources, fruit-tree plantations, and community deterrents.